Facet-Related Non-uniform Photoluminescence in Passivated GaAs Nanowires - Jiang, Nian; Joyce, Hannah J.; Parkinson, Patrick; Wong-Leung, Jennifer; Tan, Hark Hoe; Jagadish, Chennupati (Frontiers in Chemistry, 2020)
The semiconductor nanowire architecture provides opportunities for non-planar electronics and optoelectronics arising from its unique geometry. This structure gives rise to a large surface area-to-volume ratio and therefore understanding the effect of nanowire surfaces on nanowire optoelectronic properties is necessary for engineering related devices. We present a systematic study of the non-uniform optical properties of Au-catalysed GaAs/AlGaAs core–shell nanowires introduced by changes in the sidewall faceting. Significant variation in intra-wire photoluminescence (PL) intensity and PL lifetime (τ_PL) was observed along the nanowire axis, which was strongly correlated with the variation of sidewall facets from {112} to {110} from base to tip. Faster recombination occurred in the vicinity of {112}-oriented GaAs/AlGaAs interfaces. An alternative nanowire heterostructure, the radial quantum well tube consisting of a GaAs layer sandwiched between two AlGaAs barrier layers, is proposed and demonstrates superior uniformity of PL emission along the entire length of nanowires. The results emphasise the significance of nanowire facets and provide important insights for nanowire device design.